Accesibilidad peatonal a la red sanitaria de asistencia primaria en Madrid - Gutiérrez Puebla, Javier; Alventosa, Concepción; Redondo, José Carlos; Paniagua, Eloisa; García Palomares, Juan Carlos (Anales de Geografía de la Universidad Complutense, 2002)
Sin resumen